The influence of broach design on bone friction and osseodensification in total hip arthroplasty. (March 2020) - Bätz, Johanna; Syrigos, Stefan; Vorbeck, Marius; Prüch, Elena; Campbell, Graeme; Morlock, Michael
Abstract: Background: The process of cavity preparation by broaching has an impact on the primary stability of uncemented hip stems and on the periprosthetic fracture risk. Osseodensifying broaches may increase primary stability, but have the potential to raise cortex strains and facilitate fracture. The aim of this study was to determine the influence of broach design on the forces acting during broaching, on the microstructure of the broached bone bed and the amount and depth of osseodensification. Methods: Broach models representing compaction, blunt extraction and sharp extraction broaches, were used for quasi-static simulation of femoral cavity preparation on bovine trabecular bone cuboids. Broaching forces were measured and micro-computed tomography scans performed prior and after testing. Friction coefficients during broaching, bone densification parameters and size of the debris particles pushed into the bone were determined. Findings: Friction coefficients during sharp extraction exceeded those during compaction and blunt extraction broaching (by 38% and 37%, P  < .001). Total bone densification was enhanced for compaction and blunt extraction compared to sharp extraction broaching (increase of 121% and 117%, P  = .005), resulting from higher densification depths for compaction ( P  = .001) and higher maximum densification for blunt extraction broaching ( P  = .008), with the latter producing fewer large particles than compaction broaching ( P  = .005). Interpretation: Higher friction coefficients indicate a decreased periprosthetic fracture risk with sharp extraction broaches for equal implantation forces. The blunt extraction and compaction designs investigated densified the bone to a similar extent. Blunt extraction broaching may support better osseointegration due to smaller bone debris particles. Highlights: Compaction and blunt extraction broaches densify bone to a similar extent. Blunt extraction produce less large bone debris particles than compaction broaches. Sharp extraction broaches show higher coefficients of friction against bone.